PERANCANGAN APLIKASI E-SETOR (ELECTRONIC SERVICE MOTOR) MENGGUNAKAN YII2 FRAMEWORK BERBASIS RESTFUL WEBSERVICE - Manda Sari; Nurindah Dwiyani (Universitas Negeri Padang, 2019)
The development of technology has developed very rapidly in recent years. Along with its development, giving influence in various sectors, both government agencies, industry and the business world. One of them is in the motorbike service business. The desire of customers to get good and fast service makes business people to be able to improve services as much as possible. One way that can be done is by using a system that can be accessed by customers using a mobile phone. Applications that are built using the Yii 2 framework are based on a restful web service. The Yii Framework makes the appearance of the system more neat, organized and high-performance. The appearance of this application is user friendly so it does not cause difficulties when customers access the system. The programming languages used are HTML and PHP. The system appearance is interesting because it uses bootstrap which is combined with CSS. Applications that are built using the waterfall method. There are several stages that exist in this method, including system requirements analysis, system design, code making and testing. The purpose of designing this application is to improve service and provide customer satisfaction for both companies and users. Keywords: Motorcycle Service Business, Yii Framework, Restful Web Sevice